Gamification, Scaffolding and Integrative Background: Toward an Inclusive Education Model - Valentina Della Volpe (European Scientific Journal, ESJ, 2025)
This article investigates the theoretical interconnections among gamification, Bruner’s concept of scaffolding, and the Italian pedagogical method of the integrative background, examining their potential in fostering personalized and inclusive education. Based on a critical synthesis of theoretical and empirical contributions from recent literature, the study highlights how the convergence of these methodologies can enhance motivation, cognitive development, and active engagement in diverse educational settings. Gamification is analyzed as a tool that fosters engagement and persistence through playful learning dynamics, acting as motivational scaffolding. Scaffolding, as conceptualized by Bruner and enriched by Vygotsky’s contributions, is presented as a flexible support process that adapts to students’ evolving cognitive and emotional needs. The integrative background, sfondo integratore, as developed by Canevaro and Zanelli, is presented as a contextualized methodology that fosters shared meaning-making and reduces barriers to learning and creates inclusive learning environments. Based on these analyses, the paper proposes a theoretical model that integrates gamification, scaffolding, and the integrative background into a coherent educational framework. This model aims to support inclusive practices by promoting meaningful, differentiated learning pathways and improving participation and academic achievement for all learners. The study offers methodological insights for the design of inclusive teaching practices and reflects on the transformative potential of integrating game-based, scaffolded, and narrative-driven learning strategies across diverse educational contexts.